Manipulating the tumor immune microenvironment to improve cancer immunotherapy: IGF1R, a promising target - Pellegrino, Marsha; Secli, Valerio; D’Amico, Silvia; Petrilli, Lucia Lisa; Caforio, Matteo; Folgiero, Valentina; Tumino, Nicola; Vacca, Paola; Vinci, Maria; Fruci, Doriana; de Billy, Emmanuel (Frontiers in Immunology, 2024)
Cancer immunotherapy has made impressive advances in improving the outcome of patients affected by malignant diseases. Nonetheless, some limitations still need to be tackled to more efficiently and safely treat patients, in particular for those affected by solid tumors. One of the limitations is related to the immunosuppressive tumor microenvironment (TME), which impairs anti-tumor immunity. Efforts to identify targets able to turn the TME into a milieu more auspicious to current immuno-oncotherapy is a real challenge due to the high redundancy of the mechanisms involved. However, the insulin-like growth factor 1 receptor (IGF1R), an attractive drug target for cancer therapy, is emerging as an important immunomodulator and regulator of key immune cell functions. Here, after briefly summarizing the IGF1R signaling pathway in cancer, we review its role in regulating immune cells function and activity, and discuss IGF1R as a promising target to improve anti-cancer immunotherapy.